FACTORS INFLUENCING HUMAN RELIABILITY OF HIGH TEMPERATURE GAS COOLED REACTOR OPERATION - Sigit Santoso (Pusat Teknologi Dan Keselamatan Reaktor Nuklir (PTKRN), 2016)
ABSTRACT Operator roles and intervene actions on the operation of gas cooled reactor would be different compared to their roles in other reactor types. Analysis of operator performance and the influencing factors can be conducted comprehensively in Human Reliability Analysis (HRA). Using HRA, the impact of human errors on the system and the ways to reduce human error impact and frequency can be idenfified. The paper discusses factors influencing reactor operator performance to response to the cooling accident of the high temperature gas cooled reactor (HTGR). Analysis and qualification of influencing factors, which are performance shaping factors (PSF), were conducted based on time reliability curve and Cognitive Reliability and Error Analysis Method (CREAM). Based on time reliability curve, results showed that time variable contributes to the improvement of operator performance (PSF<1), especially when the safety features of the system properly work as in the design. Based on CREAM, it can be identified that in addition to the time variable, human machine interface design and sufficiently training also contribute to the improvement of operator performance. This study found that total PSF equals to 0.25, in which the positive dominant factor is time variable whose PSF is 0.01 and the negative dominant factors are procedure and working cycle whose PSF is 5. Those PSF values reflected the multiplier factors to the human error probability. The analysis of performance shaping factors should be developed on the other operation and accident scenarios of HTGRs prior to be further applied for a comprehensive assessment and analysis of human reliability and for the design of human machine interface system at control room. Keywords: PSF, HTGR, human operator, control room, human reliability ABSTRAK Peran dan tindakan operator pada reaktor berpendingin gas akan berbeda dengan peran operator pada operasi tipe reaktor lain. Analisis unjuk kerja operator dan faktor yang berpengaruh dapat dilakukan secara komprehensif melalui analisis keandalan manusia(HRA). Melalui HRA dampak dari kesalahan manusia pada sistem maupun cara untuk mengurangi dampak dan frekuensi kesalahan dapat diketahui. Makalah membahas faktor yang berpengaruh pada tindakan operator, yaitu pada kejadian kecelakaan pendingin reaktor gas bersuhu tinggi-HTGR. Analisis untuk kualifikasi faktor pembentuk kinerja(PSF) dilakukan berdasarkan kurva keandalan fungsi waktu, dan metode keandalan manusia yang dikembangkan berdasar pada aspek kognitif yaitu Cognitive Reliability and Error Analysis Method (CREAM). Hasil analisis berdasar kurva keandalan fungsi waktu menunjukkan komponen waktu berkontribusi positif pada peningkatan keandalan operator (PSF<1) pada kondisi semua fitur keselamatan berfungsi sesuai rancangan. Sedangkan pada metoda analisis dengan pendekatan kognitif CREAM diketahui selain faktor ketersediaan waktu, faktor pelatihan dan rancangan HMI juga berkontribusi meningkatkan keandalan operator. Faktor pembentuk kinerja keseluruhan diketahui sebesar 0,25 dengan faktor kontribusi positif dominan atau berpengaruh pada penurunan kesalahan manusia adalah ketersediaan waktu (PSF=0,01), dan faktor kontribusi negatif dominan adalah prosedur dan siklus kerja (PSF=5). Nilai PSF tersebut sebagai faktor pengali dalam perhitungan probabilitas kesalahan manusia. Analisis faktor pembentuk kinerja perlu dikembangkan pada skenario kejadian lain untuk selanjutnya digunakan untuk perhitungan dan analisis keandalan manusia yang komprehensif dan perancangan sistem interaksi manusia mesin di ruang kendali. Kata kunci: PSF, HTGR, operator, ruang kendali, keandalan manusia